Meta Analysis: The Effect of Using Mathematics Learning Media to Students’ Mathematical Abilities. - Winda Lestari; Muliawan Firdaus (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to determine : (1) The effect size of using mathematic learning media to students’ mathematical abilities as a whole, (2) The effect size of using mathematics learning media to students’ mathematical abilities based on level of education, (3) The effect size of using mathematics learning media to students’ mathematical abilities based on learning media used, (4) The effect size of using mathematics learning media to students’ mathematical abilities based on subject matter, (5) The effect size of using mathematics instructional media to students’ mathematical abilities based on quantified mathematical ablility. This research used meta analysis method. The sampling technique used purposive sampling and obtained 17 research that fit the criteria. Data collection techniques used documentation with the support of software publish or perish. The results of data analysis showed that : (1) Overall using the learning media has a large effect to students’ mathematical abilities as a proportion 0,972, (2) Based on level of education, the use of learning media has a largest effect size if applied at SMP/MTs as a proportion 1,039 (n=16, SD=0,754), (3) Based on learning media used, the visual media has a largest effect size to students’ mathematical abilities as a proportion 1,003 (n=13, SD=0,641), (4) Based on material that is taught, the use of learning media on a branch of logic material has a largest effect size to matematical abilities as a proportion 1,237 (n=2, SD=0,489), (5) Based on quantified mathematical abilities, the use of learning media has a largest effect size to students’ reasoning abilities as a proportion 1,303 (n=3, SD=0,353).